Had the Remains of S. Darius and S. Girenas Been Ever Lost? Their “Discovery” and Burial in LCP’s and KGB’s Shadow in 1958–1964 - Sviderskytė, Gražina (Lietuvos istorijos studijos, 2016)
This article reveals the secret role of the Soviet Lithuania Communist Party (LCP) and KGB in a notorious story of finding and burial of the embalmed and concealed physical remains of the American–Lithuanian transatlantic pilots Stephen Darius and Stanley Girch-Girenas (killed in the plane crash in Nazi Germany on July 17, 1933).The research was focused on the reconstruction of the chronology of events since the first public notion about the place of concealment of the pilots’ bodies in 1958 to their replacement to (rather short stop at) forensic research facilities and burial in 1964. The main problem solved was a seemingly contradicting change of the historical perception exactly at this juncture: how and why did the American pilots of Lithuanian descent, the American citizens and veterans of the American Army, become representatives of the Soviet working people?The author questioned the traditional approach, as if since 1945 the Soviets only suppressed the memory of Darius and Girenas: perhaps they even intended to destroy their physical remains and accordingly to interdict any related acts of commemoration; and if so, then the discovery of pilots’ bodies was nothing less than a heroic act of brave Lithuanian patriots? The analysis of the abundant material suggested right the opposite: that the place of concealment became known to NKVD/MGB since late 1945 or 1953 the latest, thus the access to it was secured for the right moment and for the loyal individuals only. In June 1958, having sufficient knowledge in disposition and following Moscow’s political directives, the LCP Central Committee approved and projected the revelation of the concealment. Consequently, its “discovery” was carried out in 1963 and finalized with burial in 1964, under the secret supervision of top ranking LCP and KGB officials in Vilnius and Kaunas. The transformed memory about Darius and Girenas was successfully introduced through numerous acts of “reasonable” commemoration, which were rather strictly coordinated fallacious performances, the imitation of respect to the historical truth. The result proved to be an effective “ideological weapon”, which served for decades in the interests of Soviet politics and security, domestically and abroad.
Keywords: S. Darius; S. Girenas; memory management; memory culture; memory politics; Khrushchev era; propagandistic discourse; LSSR KGB; Lithuanian Communist Party (LCP)